Facilitating Second Language Acquisition through Digital Storytelling - Baskara, F.X. Risang (Universitas Sanata Dharma, 2015)
This study was conducted to investigate the experiences of students who used digital storytelling to facilitate second language acquisition with English as a Foreign Language (EFL) students in university. Thirty students enrolled in an EFL English Speaking class in university level participated in this study. Presentation scores, notes on preparation and presentation, and teachers' reports showed that the EFL students made improvement in their acquisition of the English language after approximately four weeks of instruction and reports were given regarding the role of digital storytelling in that instruction. It was concluded that digital storytelling can enhance students’ motivation and confidence in using the English language to make a classroom presentation and can assist with language acquisition in EFL students.